Cobalt hybrid material for photocatalytic degradation of tetracycline as well as preparation method and application of cobalt hybrid material

Through the coordinated degradation of cobalt hybrid materials and PMS, and the use of photocatalytic activation of PMS, the problem of low degradation efficiency of tetracycline in water is solved, and efficient and stable degradation effect is achieved, which is suitable for the removal of tetracycline in water environment.

CN119140166APending Publication Date: 2024-12-17NANHUA UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411321627.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently degrade tetracycline in water, and the free radical half-life of the activator PMS in advanced oxidation technology is short, making it difficult to continuously produce oxidants, resulting in low degradation efficiency.

Method used

The cobalt hybrid material is used to assemble into a two-dimensional planar structure through an aromatic carboxylic acid linker as a photocatalyst to synergize tetracycline with PMS, and activate PMS by light irradiation to improve degradation efficiency.

Benefits of technology

The 99% degradation rate of tetracycline was achieved within 10 minutes, and the degradation rate was still 90% after 4 recycles. The material is highly stable and easy to recover, and is suitable for efficient degradation in water environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119140166A_ABST
    Figure CN119140166A_ABST
Patent Text Reader

Abstract

The invention discloses a cobalt hybrid material for photocatalytic degradation of tetracycline as well as a preparation method and application of the cobalt hybrid material, and relates to the technical field of degradation of antibiotics in water. According to the cobalt hybrid material for photocatalytic degradation of tetracycline, two-core cobalt is used as a basic structure unit, aromatic carboxylic acid is used as a connector, and a two-dimensional plane structure is assembled. The cobalt hybrid material has good stability, can be used as a photocatalytic material to efficiently activate PMS, and can cooperate with PMS to degrade tetracycline in water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of antibiotic degradation in water bodies, and in particular to a cobalt hybrid material for photocatalytic degradation of tetracycline, and a preparation method and application thereof. Background Art

[0002] Tetracycline antibiotics are the most widely used and frequently used antibiotics, and are widely used in medicine, animal husbandry and other fields. Tetracycline molecules contain four parallel rings, which are complex and stable in structure and difficult to be completely absorbed and degraded. They will inevitably enter the environment and accumulate in the environment. If humans are exposed to or ingest tetracycline for a long time, they may develop corresponding resistance genes. In addition, due to the toxicity, carcinogenicity, mutagenicity and interference with the endocrine system of tetracycline, it will pose a huge threat to human health and ecological security.

[0003] In order to protect human health and ecological environment safety, researchers have developed a variety of methods for degrading tetracycline, including biological, physical and chemical methods. These methods have some disadvantages, such as the adsorption method only transfers antibiotics from liquid to solid phase, cannot degrade antibiotics and the secondary use of adsorbents is difficult, the chemical method is prone to secondary pollution, and the biodegradation method is costly and not suitable for highly toxic environments, which has great limitations. Therefore, how to safely and efficiently remove tetracycline from the ecosystem has become an urgent problem to be solved.

[0004] Advanced oxidation technology is widely used in antibiotic removal due to its advantages such as fast removal rate, high degradation efficiency, no secondary pollution and simple operation. It has great application prospects in tetracycline degradation. At present, advanced oxidation technology (AOPs) based on activated permonosulfate (PMS) has attracted widespread attention for the removal of tetracycline in water. PMS is a strong oxidant that is easily activated to produce SO4 under external stimulation. •- , •OH and O2 •- Free radicals such as SO4 can effectively degrade organic pollutants. However, the half-life of free radicals is relatively short, such as SO4 •- , •OH and O2 •- The half-lives of PMS are 30-40 μs, 20 ns and 1 s respectively. Therefore, how to efficiently activate PMS to quickly and continuously produce more free radicals is the key to the degradation of tetracycline by PMS advanced oxidation method. Summary of the invention

[0005] One of the purposes of the present invention is to provide a cobalt hybrid material which has good stability and can be used as a photocatalytic material to efficiently activate PMS and synergistically degrade tetracycline in water with PMS.

[0006] In order to achieve the above object, the present invention adopts the following technical scheme: a cobalt hybrid material for photocatalytic degradation of tetracycline, which is composed of dinuclear cobalt as a basic structural unit and is assembled into a two-dimensional planar structure through aromatic carboxylic acid as a connector.

[0007] The above cobalt hybrid material can be prepared by the following steps: Dissolve an appropriate amount of cobalt metal salt, carboxylic acid ligand, and pyridine ligand in an organic solvent, react at 70-105°C (preferably 105°C) for 24-72 hours (preferably 72 hours), cool and filter, and then stand for 3-7 days (preferably 3 days) to obtain crystals (usually purple-red crystals), which are the target product.

[0008] In the step of preparing the cobalt hybrid material, the molar ratio of the cobalt metal salt, the carboxylic acid ligand, and the pyridine ligand is 1:(1-2):(1-2). Preferably, the molar ratio of the cobalt metal salt, the carboxylic acid ligand, and the pyridine ligand is 1:1:1 or 1:1.5:1.5 or 1:2:2.

[0009] In the step of preparing the cobalt hybrid material, the cobalt metal salt is selected from at least one of nitrate and acetate, the carboxylic acid ligand is naphthalene dicarboxylic acid, and the pyridine ligand is o-phenanthroline. Preferably, the cobalt metal salt is a nitrate (e.g., cobalt nitrate hexahydrate) or an acetate (e.g., cobalt acetate).

[0010] In the step of preparing the cobalt hybrid material, the organic solvent is a mixed solvent of N,N-dimethylformamide, dimethyl sulfoxide, ethanol and water.

[0011] Among them, every 0.05mmol of cobalt metal salt, 0.05-0.1mmol of carboxylic acid ligand, and 0.05-0.1mmol of pyridine ligand corresponds to 2mL of N,N-dimethylformamide, 2mL of dimethyl sulfoxide, 6ml of ethanol, and 2ml of water.

[0012] Preferably, every 0.05 mmol of cobalt metal salt, 0.05 mmol of carboxylic acid ligand, and 0.05 mmol of pyridine ligand corresponds to 2 mL of N,N-dimethylformamide, 2 mL of dimethyl sulfoxide, 6 ml of ethanol, and 2 ml of water.

[0013] In the preparation step of the cobalt hybrid material, after the heating reaction (i.e., after reacting at 70-105°C for 24-72 hours), the temperature can be programmed to cool to room temperature, and the cooling rate can be controlled at 5-10°C / h (preferably 5°C / h).

[0014] Room temperature generally refers to the current air temperature during preparation (experiment), such as 10 to 40°C (preferably 25 to 35°C, more preferably 25°C or 30°C or 35°C).

[0015] In the preparation step of the cobalt hybrid material, after the cobalt metal salt, carboxylic acid ligand, and pyridine ligand are dissolved in an organic solvent, they can be stirred evenly at a stirring temperature of 25 to 35° C. (i.e., the current room temperature during the experiment, such as 25° C., 30° C., 35° C.), and a stirring time of 30 to 60 min (preferably 30 min).

[0016] In the step of preparing the cobalt hybrid material, the heating reaction can be carried out in a reaction vessel, such as a reactor.

[0017] In the preparation step of the cobalt hybrid material, after cooling and filtering, the filtrate is left to stand for 3 to 7 days to grow crystals. After the crystals grow, the filtrate can be filtered, washed and dried to obtain the cobalt hybrid material.

[0018] Specifically, the steps for preparing the cobalt hybrid material include: (1) Dissolve the cobalt metal salt, carboxylic acid and pyridine ligand in an organic solvent for later use; (2) Transfer the solution to a reactor, react at 70-105°C for 24-72 hours, and then cool to room temperature; (3) Filter and let the filtrate stand for 3-7 days to allow crystals to grow; (4) Filter, wash and dry to obtain the cobalt hybrid material.

[0019] In step (4), the solvent used for washing can be N,N-dimethylformamide and water, and the number of washing times is not limited to once, but can also be multiple times, for example, three times.

[0020] In step (4), the drying temperature after filtration is room temperature to 50°C, for example, 10 to 50°C (preferably 25 to 50°C, more preferably 25°C, 30°C, 35°C or 50°C).

[0021] Among them, cobalt hybrid materials are also called cobalt complexes, and complexes are also called organic-inorganic hybrid materials.

[0022] In addition, the above-mentioned cobalt hybrid material can also be used in the degradation of tetracycline.

[0023] Furthermore, the cobalt hybrid material and PMS synergistically degrade tetracycline.

[0024] The step of degrading tetracycline includes: The cobalt hybrid material and the PMS solution are sequentially added into the tetracycline aqueous solution, reacted under light irradiation conditions, and the tetracycline in the tetracycline aqueous solution is catalytically degraded.

[0025] The light irradiation can be natural light irradiation or irradiation with lighting equipment, and natural light irradiation is preferred.

[0026] Among them, PMS is permonosulfate, also known as peroxymonosulfate, which can be sodium persulfate or potassium persulfate.

[0027] Among them, every 2.5 mg of cobalt hybrid material corresponds to 0.025 mmol of PMS.

[0028] Further, every 50 ml of the tetracycline aqueous solution corresponds to 2.5 mg of the cobalt hybrid material and 0.025 mmol of PMS.

[0029] In the step of degrading tetracycline, the mass concentration of the cobalt hybrid material is 0.05-0.2 g / L (preferably 0.1 g / L), the concentration of the PMS solution is 0.3-2 mmol / L (preferably 1 mmol / L), and the concentration of the tetracycline aqueous solution is 10-50 mg / L (preferably 10 mg / L).

[0030] In the step of degrading tetracycline, the cobalt hybrid material and the PMS solution are sequentially added to the tetracycline aqueous solution and stirred. The stirring can be performed in a constant temperature water bath, and the temperature of the constant temperature water bath is controlled to be 20-40°C (preferably 40°C).

[0031] In addition, after the tetracycline is catalytically degraded, the cobalt hybrid material can be centrifuged, washed, and recovered. Specifically, after the tetracycline degradation experiment is completed, centrifuge for 10 minutes, pour off the supernatant, collect the cobalt hybrid material and wash it with water and ethanol (the number of washings is not limited to once, and can also be multiple times, such as 3 times), and then dry it for reuse.

[0032] Specifically, the steps of catalytic degradation of tetracycline include: The crystals of the cobalt hybrid material are ground into powder, added to the tetracycline solution, stirred in a constant temperature water bath, and then PMS is added under natural light. The cobalt hybrid material can be used as a photocatalytic material to synergistically degrade pollutants in water with PMS to achieve efficient degradation of tetracycline. After the degradation is completed, the cobalt hybrid material catalyst is centrifuged, washed, and recovered.

[0033] The present invention constructs a two-nuclear cobalt as a basic structural unit, uses an aromatic carboxylic acid as a connector, and self-assembles into a two-dimensional plane stable structure to obtain a solid catalyst (i.e., a cobalt hybrid material) that has both suitable water stability and the ability to efficiently activate PMS. The synthesis steps of the cobalt hybrid material are simple, the yield is high, and it has excellent catalytic performance. It can efficiently activate PMS, and the efficiency of catalytic degradation of tetracycline in 10 minutes can reach 99%. The degradation rate after recycling 4 times can still reach 90%. Moreover, the cobalt hybrid material of the present invention has high stability, is easy to recycle, and can be reused. It can be used as a photocatalytic material to synergistically degrade tetracycline pollutants in water with PMS. The reaction conditions are mild, the degradation efficiency is high, and it is easy to recycle. It has a good application prospect and can be used for the efficient degradation of tetracycline in water environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a crystal photo of cobalt hybrid material; Figure 2 This is the microstructure diagram of the cobalt hybrid material; Figure 3 The thermogravimetric curve and DTG curve of the cobalt hybrid material; Figure 4 is the degradation rate curve of tetracycline; Figure 5 This is a graph of the recycling performance of cobalt hybrid materials; Figure 6 This is the X-ray powder diffraction pattern (XRD) of the cobalt hybrid material. DETAILED DESCRIPTION

[0035] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with the examples, and the contents mentioned in the examples are not limitations of the present invention. It should be noted in advance that the following examples were completed in the laboratory, and those skilled in the art should understand that the amounts of the components given in the examples only represent the ratio relationship between the components, rather than specific limitations. Example 1

[0036] Dissolve 0.05mmol naphthalene dicarboxylic acid, 0.05mmol o-phenanthroline and 0.05mmol cobalt metal salt (cobalt nitrate hexahydrate is selected in this embodiment) in 2mL N,N-dimethylformamide, 2mL dimethyl sulfoxide, 6ml ethanol and 2ml water, stir at a magnetic stirring speed of 200-500r / min (300r / min in this embodiment), and stir at room temperature (30°C in this embodiment) for 30-60min (30min in this embodiment). Transfer the stirred solution to a 20mL reactor and keep it at 70-105°C (105°C in this embodiment) for 24-72 hours (72 hours in this embodiment). The mixture was cooled to 30°C at a cooling rate of 5-10°C / h (5°C / h in this embodiment), taken out and filtered, and the filtrate was allowed to stand for 3-7 days (3 days in this embodiment) to obtain purple-red crystals (i.e., the target product, cobalt hybrid material). The crystals were washed with N,N-dimethylformamide and water, dried at room temperature, and weighed. The yield was 85%. Example 2

[0037] Dissolve 0.05mmol naphthalene dicarboxylic acid, 0.05mmol o-phenanthroline and 0.05mmol cobalt metal salt (cobalt acetate is selected in this embodiment) in 2mL N,N-dimethylformamide, 2mL dimethyl sulfoxide, 6ml ethanol and 2ml water, stir at a magnetic stirring speed of 200-500r / min (300r / min in this embodiment), and stir at room temperature (30°C in this embodiment) for 30-60min (30min in this embodiment). Transfer the stirred solution to a 20mL reactor and keep it at 70-105°C (105°C in this embodiment) for 24-72 hours (72 hours in this embodiment). The mixture was cooled to 30°C at a cooling rate of 5-10°C / h (5°C / h in this embodiment), taken out and filtered, and the filtrate was allowed to stand for 3-7 days (3 days in this embodiment) to obtain purple-red crystals (i.e., the target product, cobalt hybrid material). The crystals were washed with N,N-dimethylformamide and water, dried at room temperature, and weighed. The yield was 88%. Example 3

[0038] Dissolve 0.075mmol naphthalene dicarboxylic acid, 0.075mmol o-phenanthroline and 0.05mmol cobalt metal salt (cobalt nitrate hexahydrate is selected in this embodiment) in 2mL N,N-dimethylformamide, 2mL dimethyl sulfoxide, 6ml ethanol and 2ml water, stir at a magnetic stirring speed of 200-500r / min (200r / min in this embodiment), and stir at room temperature (25°C in this embodiment) for 30-60min (50min in this embodiment). Transfer the stirred solution to a 20mL reactor and keep it at 70-105°C (70°C in this embodiment) for 24-72 hours (24 hours in this embodiment). The mixture was cooled to 25°C at a cooling rate of 5-10°C / h (8°C / h in this embodiment), taken out and filtered, and the filtrate was allowed to stand for 3-7 days (5 days in this embodiment) to obtain purple-red crystals (i.e., the target product, cobalt hybrid material). The crystals were washed with N,N-dimethylformamide and water, and dried at room temperature. Example 4

[0039] Dissolve 0.1mmol naphthalene dicarboxylic acid, 0.1mmol o-phenanthroline and 0.05mmol cobalt metal salt (cobalt nitrate hexahydrate is selected in this embodiment) in 2mL N,N-dimethylformamide, 2mL dimethyl sulfoxide, 6ml ethanol and 2ml water, stir at a magnetic stirring speed of 200-500r / min (500r / min in this embodiment), and stir at room temperature (35°C in this embodiment) for 30-60min (60min in this embodiment). Transfer the stirred solution to a 20mL reactor and keep it at 70-105°C (90°C in this embodiment) for 24-72 hours (42 hours in this embodiment). The mixture was cooled to 35°C at a cooling rate of 5-10°C / h (10°C / h in this embodiment), taken out and filtered, and the filtrate was allowed to stand for 3-7 days (7 days in this embodiment) to obtain purple-red crystals (i.e., the target product, cobalt hybrid material). The crystals were washed with N,N-dimethylformamide and water and dried at room temperature.

[0040] The present invention also conducted a catalytic degradation experiment of tetracycline on the target product (cobalt hybrid material) of Example 1: Weigh 2.5 mg of cobalt hybrid material powder, add it to 50 ml of 10 mg / L tetracycline aqueous solution, place in a 40°C constant temperature water bath, and stir for 30 minutes in the dark to achieve adsorption-desorption equilibrium. Then, add 0.025 mmol of PMS solution (potassium persulfate solution was used in this experiment) under natural light irradiation and continue stirring. Samples were taken every 2 minutes, filtered with a 0.22 micron filter, and then measured by UV-visible spectrophotometer to measure the maximum absorption wavelength (λ TC =355nm, TC is tetracycline) at which the removal rate of tetracycline at different times was obtained.

[0041] The present invention also conducted a recycling experiment on the target product (cobalt hybrid material) of Example 1: Weigh 2.5 mg of cobalt hybrid material powder, add it to 50 ml of tetracycline aqueous solution with a concentration of 10 mg / L, keep it in a constant temperature water bath at 40 ° C, and stir it for 30 minutes under light-proof conditions to achieve adsorption-desorption equilibrium. Then, under the irradiation of natural light, add 0.025 mmol of PMS solution (potassium persulfate solution is selected in this experiment) and continue stirring. Take 3 mL of sample every 2 minutes, filter it with a 0.22 micron filter head, and measure it by UV-visible spectrophotometer. After the experiment is completed, centrifuge the solution, remove the supernatant, collect the solid, wash it with deionized water and ethanol 3 times, and then dry it. Repeat the above steps for the dried solid. After repeating the experiment 4 times, the efficiency of tetracycline degradation by the cobalt hybrid material is still as high as 90%. The cobalt-based complex (i.e., cobalt hybrid material) after use is collected for powder diffraction test (XRD), and its structure remains intact.

[0042] The crystal photos prepared in Example 1 can be found in Figure 1 .

[0043] The crystal prepared in Example 1 was collected using a single crystal X-ray diffractometer and the structure was analyzed using Olex2 software. Figure 2 As shown, the crystal prepared in Example 1 is a cobalt hybrid material, which is composed of two cobalt basic units, self-assembled into a stable two-dimensional planar structure through a naphthalene dicarboxylic acid linker. Figure 6 As shown in Figure 2, the simulated peaks of XRD are consistent with the test peaks, indicating that the obtained cobalt hybrid material is pure phase and can be used for structural characterization and performance testing, and its structure after catalysis remains intact. Figure 3 As shown, the cobalt hybrid material has good thermal stability and can exist stably before 340℃.

[0044] like Figure 4 As shown in the figure, the first line is a blank sample (no catalyst is added to the tetracycline aqueous solution), the second line is the degradation of tetracycline by the cobalt hybrid material catalyst alone without PMS, and the degradation effect is poor; the third line is the degradation of tetracycline by PMS alone without the addition of the cobalt hybrid material (labeled as Co2) catalyst, and the degradation effect is not ideal, while the fourth line is the synergistic catalytic degradation of tetracycline by the cobalt hybrid material / PMS system, and the degradation effect is significantly better than other samples. It can be seen that after adding the cobalt hybrid material, the catalytic degradation effect has been greatly improved. Moreover, the degradation rate of tetracycline in the cobalt hybrid material / PMS system can reach 99% within 10 minutes.

[0045] like Figure 5 As shown, after repeated use for 4 times, the catalytic degradation rate of tetracycline by the cobalt hybrid material is still as high as 90%.

[0046] In general, the present invention prepares cobalt hybrid materials by a solvothermal method, and the preparation method is simple and efficient. The prepared cobalt hybrid materials have high yield, good stability, and are easy to recycle. The cobalt hybrid materials can be used as photocatalytic materials to synergistically degrade pollutants in water with permonosulfate PMS, with mild reaction conditions and high degradation efficiency. In the experiment of degrading tetracycline, the degradation efficiency within 10 minutes is 99%, and the degradation rate can still reach 90% after being recycled for 4 times. It has good application prospects and can be used for the efficient degradation of tetracycline in actual water environments.

[0047] The above embodiments are preferred implementation schemes of the present invention. In addition, the present invention may also be implemented in other ways. Any obvious replacement without departing from the concept of the present technical solution is within the protection scope of the present invention.

[0048] Finally, it should be emphasized that in order to allow ordinary technicians in the field to more easily understand the improvements of the present invention over the prior art, some descriptions of the present invention have been simplified, and for the sake of clarity, some other elements are omitted in this application document. Those skilled in the art should realize that these omitted elements may also constitute the content of the present invention.

Claims

1. A cobalt hybrid material for photocatalytic degradation of tetracycline, characterized in that: This material uses dinuclear cobalt as the basic structural unit and is assembled into a two-dimensional planar structure through aromatic carboxylic acids as connectors.

2. The method for preparing the cobalt hybrid material for photocatalytic degradation of tetracycline according to claim 1, characterized in that: The following steps are involved: Dissolve appropriate amounts of cobalt metal salt, carboxylic acid ligand and pyridine ligand in an organic solvent, react at 70-105°C for 24-72 hours, cool, filter and stand for 3-7 days to obtain crystals, which are the target product.

3. The method for preparing a cobalt hybrid material for photocatalytic degradation of tetracycline according to claim 2, characterized in that: The molar ratio of the cobalt metal salt, the carboxylic acid ligand and the pyridine ligand is 1:(1-2):(1-2).

4. The method for preparing a cobalt hybrid material for photocatalytic degradation of tetracycline according to claim 2, characterized in that: The cobalt metal salt is selected from at least one of nitrate and acetate, the carboxylic acid ligand is naphthalene dicarboxylic acid, and the pyridine ligand is o-phenanthroline.

5. The method for preparing the cobalt hybrid material for photocatalytic degradation of tetracycline according to claim 2, characterized in that: The organic solvent is a mixed solvent of N,N-dimethylformamide, dimethyl sulfoxide, ethanol and water.

6. Use of the cobalt hybrid material for photocatalytic degradation of tetracycline according to claim 1 in the degradation of tetracycline.

7. Use of the cobalt hybrid material for photocatalytic degradation of tetracycline according to claim 6 in the degradation of tetracycline, characterized in that: The cobalt hybrid material and PMS synergistically degrade tetracycline.

8. The use of the cobalt hybrid material for photocatalytic degradation of tetracycline according to claim 7 in the degradation of tetracycline, characterized in that: The cobalt hybrid material and PMS are sequentially added into a tetracycline aqueous solution, reacted under light irradiation conditions, and catalytically degraded the tetracycline in the tetracycline aqueous solution.

9. Use of the cobalt hybrid material for photocatalytic degradation of tetracycline according to claim 7 or 8 in the degradation of tetracycline, characterized in that: Every 2.5 mg of the cobalt hybrid material corresponds to 0.025 mmol of PMS.

10. Use of the cobalt hybrid material for photocatalytic degradation of tetracycline according to claim 8 in the degradation of tetracycline, characterized in that: Each 50 ml of tetracycline aqueous solution corresponds to 2.5 mg of cobalt hybrid material and 0.025 mmol of PMS.

Citation Information

Cited By

  • Preparation method of photocatalytic degradation tetracycline doped / intercalated ZnAl-LDH catalyst

    CN122183664A